The ‘nautai’ and the promotion of the cult of Athena in Sicily in the Archaic Period - Soares, Martinho Guilherme Fonseca (Romanitas - Revista de Estudos Grecolatinos, 2020)
This article presents the condition of the ‘nautai’ as “protected” by Athena, the particularities of their craft in the field of navigation in the context of Greek expansionism towards the foundation of their ‘apoikiai’ in the western Mediterranean. It explores the challenges of navigation on the high seas and, from reading Homer’s Odyssey, how Athena was invoked by sailors from the Archaic Period in their travels. Then, he dedicated himself to mapping the temples and shrines dedicated to divinity in ‘apoikiai’ founded in Sicilian territory throughout the 8th and 6th centuries BC, seeking, finally, to highlight the elements that led to the promotion of his cult as a result of the modes of Athena’s intervention in the field of navigation ‘tékhnai’.
Keywords: Odyssey; Nautai; Athena; Sicilia; Connectivity